Modelling mode and parking choice behaviour under cordon pricing policy in mashhad central business district, Iran - Azari, Kian Ahmadi (2012)
Transportation problems such as traffic congestion, crash, pollution (air and noise) are results of increased private cars in use, especially in large metropolitan areas such as Mashhad Central Business District (CBD). For many years, parking policy in downtown areas has been considered as one of the best and efficient tool for travel demand management (TDM). Recently, road pricing has shown greater promise in alleviating congestion in urban areas, but has still to prove its worth in TDM. In previous studies, researchers focused on the role of congestion pricing and its effects on mode choice. Meanwhile, the literature has ignored studying travellers’ response to mode and parking choice behaviour in the presence of cordon pricing measures,especially in developing countries. The main objective of this research is to evaluate the effect of cordon pricing and parking policy measures on parking location and mode choice in CBD of Mashhad, Iran. This will lead to assess the effectiveness of both parking and cordon related policies aimed at implementing a good scheme in order to encourage private car users to shift mode, but not discourage visitors from coming to the city center. Two surveys were conducted to assess user’s attitudes towards Mashhad cordon pricing scheme. To determine the traffic impacts, the survey was performed before and after implementation of cordon charges in 2010. Traffic counts were done in the entrance section of the restricted zone in four major roads connected to the CBD. To develop the mode and parking choice behaviour model, a random sample size of 586 respondents was requested to perform a comprehensive questionnaire-based survey. Employing stated preference method, the drivers’ mode and parking choice behaviour were advanced by multinomial logit model, by addressing two different models; general and trip purpose-based model. Based on the traffic survey, volume of passenger cars travelling inside the cordon zone declined by 36% (12,510 vehicles per day), which caused increased volume of taxi (17.4%) and bus (26.9%). Furthermore, the daily trip distribution shows that the largest reduction of passenger car volume was observed during the afternoon peak (53%) rather than in the morning peak, which reveals that a greater portion of arbitrary trips occurred during afternoon peak. Results from the hypothetical question analysis shows that the in-vehicle cost is the least (33%) and cordon cost the most (67%) important attributes affecting mode choice. Further, the results suggest that increasing cordon and parking costs by TN3000 (TN1000= USD ($)1.0)and TN600, respectively, will drive 80% of commuters away from using private car to travel inside the cordon area. For the general mode and parking choice model, it is found that the estimated coefficients from the SP experiments (cordon/parking/in-vehicle cost, and search/egress time) were all embedded in the final model with negative signs, implying that the utility of travelling to the CBD decreases as the time and cost for car users increase. Meanwhile, drivers have high sensitivity to cordon charge (-1.145), significantly higher than to parking cost, search and egress times. Finally,drivers’ willingness to pay for parking fee is 2 to 3 times higher than for cordon toll. A comparison of purpose-based models shows that cordon cost and the thresholds of parking costs have significant effect on non-workers than on workers to shift mode. Besides, the effect of reduced travel time is more effective than increased travel cost to encourage workers to shift mode. The elasticity values for cordon (-2.262) and parking (-0.331) indicate that non-workers, due to their more flexible travel schedule are more sensitive than workers, to changes in the attributes. Finally, the willingnes stopay for workers is 2.3 times higher than for non-workers in the case of cordon charge. Overall, it is concluded that cordon pricing is an effective policy to alleviate congestion and manage travel demand in city centres. Based on the results, the study suggests policy implications for improvement of public transport services, parking at the fringe or outside the CBD, and time-wise cordon charging which would affect mode and parking location preference and result in significant reduction of car use inside the CBD.